OSTREACEA (BIVALVIA) OF THE VICTOR BENAVIDES CACERES COLECTION DEPOSSITED IN THE MUSEUM OF NATURAL HISTORY “VERA ALLEMAN HAEGHEBAERT” OF THE RICARDO PALMA UNIVERSITY, LIMA, PERÚ (UPPER CRETACEOUS, PERU) - Alleman Haeghebaert, Vera (2019)
Record of a total of eleven oysters from the Cajamarca and Ancash región, belonging to four genera: Aetostreon Bayle, 1878, Cameleolopha Vyalov, 1936, Exogyra Say, 1820 and Nicaisolopha Vyalov, 1936, all of the upper Cretaceous of the regions of Cajamarca, Chota, La Encañada and Ancash, Sihuas.  Determinación of four species: Exogyra africana Coquand, 1862 var. peruana Paulcke, 1903. Exogyra (Costagyra) olisiponensis Sharpe, 1850 var. duplex Paulcke, 1903, Exogyra mermeti (Coquand, 1862) and Nicaisolopha nicaisei Vyalov, 1936 was made.